Current Management of Testicular Cancer - Shin, Yu Seob (The Korean Urological Association, 2013)
Germ cell tumors (GCTs) of the testis are rare, but are the most common cancer in young men. GCTs may consist of one predominant histologic pattern or may represent a mixture of multiple histologic types. For treatment purposes, two broad categories are recognized: 1) pure seminoma and 2) others, which together are termed nonseminomatous GCTs (NSGCTs). In general, seminoma tends to be less aggressive, to be diagnosed at an earlier stage, and to spread predictably along lymphatic channels to the retroperitoneum before spreading hematogenously to the lung or other organs. Compared with NSGCTs, seminoma is exquisitely sensitive to radiation therapy and platinum-based chemotherapy. NSGCTs are usually mixed tumors and teratoma often exists at the sites of metastasis with other GCT elements; cure often requires chemotherapy to kill the chemosensitive-components and surgery to remove the teratomatous components. The main factors contributing to excellent cure rates of GCTs are careful staging at diagnosis; adequate early treatment using chemotherapeutic combinations, with or without radiotherapy and surgery; and very strict follow-up and salvage therapy. We review several clinical studies and summarize the current trends in the management of GCTs.